The relationship between substance abuse awareness and self-esteem in university students - Bekircan, Esra; Ün, İlyas and İşcan Ayyıldız, Neşe and Usta, Galip (Journal of Dependence, 2022)
Objective: The aim of this study was to investigate the knowledge and awareness levels of teenagers who are at risk for substance addiction about addictive substances and to determine the relationship between them and their self-esteem. Method: This descriptive study was conducted with 280 university students. In this study, Personal Information Form, Substance Addiction Awareness Scale and Coopersmith Self-Esteem Scale were used as data collection tools. Results: In this study, 48.6% of the participants did not receive any training related to substance addiction, and 7.9% of them has been used addictive substances. It was determined that the personal attitude and opinion sub-dimension of substance addiction awareness levels has been found to be at low level. Self-esteem level of the students was at a medium level and there was a significant relationship between the total score average of the self-esteem scale and substance addiction awareness. Conclusion: Self-esteem can be increased by providing primary protection in order to raise young people with high self-esteem. Also trainings on self-esteem and substance addiction can be organized.